Persepsi Konsumen dalam Melakukan Pembayaran BPJS Kesehatan dengan Menggunakan E-Wallet di Masa Pandemi Covid-19 - Cornelia Permatasari; Indrawati Yuhertiana; Nanda Wahyu Indah Kirana (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine and analyze perceptions of ease of use and perceived risk of interest in using e-wallets in BPJS Health payments and trust as a moderating variable. This research method is descriptive quantitative. The population in this study is the people of Surabaya City. This study used a purposive sampling technique with a total sample of 100 people. The results showed that perceived ease of use had a significant positive effect, while perceived risk had no effect on the intention to use e-wallets for BPJS Health payments. Trust shows being able to moderate perceptions of ease of use, but trust is not able to moderate perceived risk of interest in using e-wallets in making BPJS Health payments. Keywords: Health BPJS, E-Wallet, Trust, Consumer Perception